2019
DOI: 10.3390/atmos10110679
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Comparison of Major Sudden Stratospheric Warming Events in CESM1-WACCM and CESM2-WACCM

Abstract: After the recent release of the historical runs by community Earth system model version 2–the whole atmosphere community climate model (CESM2-WACCM), the major sudden stratospheric warming (SSW) events in this model and in its previous version (CESM1-WACCM) are compared based on a modern reanalysis (JRA55). Using the World Meteorological Organization (WMO) definition of SSWs and a threshold-based classification method that can describe the polar vortex morphology, SSWs in models and the reanalysis are further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 63 publications
2
19
0
Order By: Relevance
“…The displacement‐type SSWs are generally believed to be caused by strong planetary waves with a zonal wavenumber of 1 (wave 1), whereas the split‐type SSWs are mainly due to the enhancement of planetary waves with a zonal wavenumber of 2 (wave 2; e.g., Charlton and Polvani, 2007; Karpechko et al, 2018; Rao J et al, 2018, 2019a, 2019b). The statistical characteristics of the planetary waves during major SSWs and the two vortex types have also been verified by modeling analyses (e.g., Cao C et al, 2019; Liu SM et al, 2019). However, the polar vortices reveal different statuses before and after the central dates during some atypical events, which causes discrepancies in the classification of SSW types.…”
Section: Introductionmentioning
confidence: 73%
“…The displacement‐type SSWs are generally believed to be caused by strong planetary waves with a zonal wavenumber of 1 (wave 1), whereas the split‐type SSWs are mainly due to the enhancement of planetary waves with a zonal wavenumber of 2 (wave 2; e.g., Charlton and Polvani, 2007; Karpechko et al, 2018; Rao J et al, 2018, 2019a, 2019b). The statistical characteristics of the planetary waves during major SSWs and the two vortex types have also been verified by modeling analyses (e.g., Cao C et al, 2019; Liu SM et al, 2019). However, the polar vortices reveal different statuses before and after the central dates during some atypical events, which causes discrepancies in the classification of SSW types.…”
Section: Introductionmentioning
confidence: 73%
“…It is important for GCMs to have a sufficiently resolved stratosphere to produce a robust QBO (Charlton-Perez et al, 2013), which is not offered by most low-top CMIP6 simulations that extend only into the lower stratosphere. CESM2-WACCM has been shown to accurately model sudden-stratospheric warming events (Liu et al, 2019), and similar model configurations within CESM1-WACCM have been shown to produce a QBO representative of observations (Richter et al, 2020), which lends confidence that CESM2-WACCM is capable of simulating an accurate QBO, as well. It is uncommon for climate models to adequately simulate both an MJO and QBO, and CESM2-WACCM therefore presents a unique opportunity to test the capability of such a model to capture the relationship between the MJO and QBO, should a relationship exist within the observational record.…”
Section: Reanalysis and Global Circulation Modelmentioning
confidence: 59%
“…It is important for GCMs to have a sufficiently resolved stratosphere to produce a robust QBO (Charlton‐Perez et al, ), which is not offered by most low‐top CMIP6 simulations that extend only into the lower stratosphere. CESM2‐WACCM has been shown to accurately model sudden‐stratospheric warming events (Liu et al, ), and similar model configurations within CESM1‐WACCM have been shown to produce a QBO representative of observations (Richter et al, ), which lends confidence that CESM2‐WACCM is capable of simulating an accurate QBO, as well.…”
Section: Methodsmentioning
confidence: 84%
“…This is mainly because the anomalous activity of the polar vortex propagates downward and cooperates with the blocking high, the East Asian trough, the East Asian winter monsoon and other circulation systems in the lower atmosphere, thus having an important influence on the weather and climate changes in the troposphere (Baldwin and Dunkerton, 1999;Kodera et al, 2000;Baldwin and Dunkerton, 2001;Zhou et al, 2002;. The downward propagation of polar vortex anomaly leads to the anomalies of the Arctic Oscillation (AO) and the East Asian winter monsoon (Wang and Chen, 2010;Cao et al, 2019;Liu et al, 2019). When the AO is strong, the East Asian trough and the Siberian high are always weak, which results in the weak East Asian Winter Monsoon and the anticyclone anomaly in Northeast China, which is conducive to the water vapor transport from the Northwest Pacific to China, and then causes more precipitation in the central and eastern regions of China (Shuai et al, 2010).…”
Section: Introductionmentioning
confidence: 99%